2012
DOI: 10.1055/s-0032-1304642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise-induced Muscle Damage on Neuromuscular Function of the Quadriceps Muscle

Abstract: Exercise-induced muscle injury is commonly accompanied by a reduction of muscular strength. It has been suggested that this reduction in voluntary force is attributable to "peripheral" and "central" mechanisms within the neuromuscular system. The quadriceps muscle of 15 subjects was damaged with four bouts of 25 maximal voluntary concentric-eccentric contractions at a speed of 60°/s. In a time period of 7 days, we investigated the contribution of agonist muscle activation and contractile properties (CP) to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 25 publications
6
39
3
1
Order By: Relevance
“…Additionally, the slowing of +dT/dt was consistent with previous studies (Behrens et al, 2012;Sayers et al, 2003) and could be the result of impairments in excitationcontraction coupling (Warren et al, 1993) and/or a shift in the length-tension relationship such that maximal force production would occur at longer muscle lengths (Prasartwuth et al, 2006). In agreement with previous findings (Behrens et al, 2012;Hubal et al, 2007), motor-unit recruitment was unaffected by EIMD in the present study-suggesting muscle soreness/pain did not prevent participants from fully activating/recruiting the damaged muscle group. The reductions in TT and +dT/dt in combination with no changes in%ACT support the idea damage to the contractile apparatus was the primary factor contributing to the observed declines in strength.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the slowing of +dT/dt was consistent with previous studies (Behrens et al, 2012;Sayers et al, 2003) and could be the result of impairments in excitationcontraction coupling (Warren et al, 1993) and/or a shift in the length-tension relationship such that maximal force production would occur at longer muscle lengths (Prasartwuth et al, 2006). In agreement with previous findings (Behrens et al, 2012;Hubal et al, 2007), motor-unit recruitment was unaffected by EIMD in the present study-suggesting muscle soreness/pain did not prevent participants from fully activating/recruiting the damaged muscle group. The reductions in TT and +dT/dt in combination with no changes in%ACT support the idea damage to the contractile apparatus was the primary factor contributing to the observed declines in strength.…”
Section: Discussionsupporting
confidence: 92%
“…A potential key component that may contribute to the impaired power production following lengthening contractions is the rate of torque development (RTD) (Andersen and Aagaard 2006). The reduction in MVC following fatigue or lengthening contractions is associated with impaired RTD (Behrens et al 2012;Crameri et al 2007;Hannah et al 2012), and this would be manifested during dynamic contractions such that the ensuing angular velocity and power production will be reduced when the contractile torque equals and then exceeds the specific isotonic load.…”
Section: Introductionmentioning
confidence: 99%
“…The NWRT can be considered as an outcome measure reflecting centrally mediated mechanisms, while local (i.e., TA muscle) muscle oxygenation can be seen as a peripherally (localized) mediated mechanism. Previous studies demonstrated the RBE on isolated eccentric contraction of elbow flexors (Muthalib et al 2011) and knee extensors (Behrens et al 2012), but no previous study has examined the contralateral repeated bout effect of TA. In the present study, TA muscle was chosen due to its muscle action, fiber composition, and activation profile (Johnson et al 1973;Madeleine et al 2006) and also because of its appropriateness for NWR recordings (Andersen 2007).…”
Section: Introductionmentioning
confidence: 99%